A study of 1088 consecutive cases of electrolyte abnormalities in oncology phase I trials. (November 2018) - Ingles Garces, Alvaro H.; Ang, Joo Ern; Ameratunga, Malaka; Chénard-Poirier, Maxime; Dolling, David; Diamantis, Nikolaos; Seeramreddi, Satyanarayana; Sundar, Raghav; de Bono, Johann; Lopez, Juanita; Banerji, Udai
Abstract: Background: The incidence and clinical significance of electrolyte abnormalities (EAs) in phase I clinical trials are unknown. The objective of this study is to evaluate the incidence and severity of EAs, graded according to CTCAE, v4.03, to identify variables associated with EAs and their prognostic significance in a phase I population. Methods: A retrospective chart review was performed of 1088 cases in 82 phase I clinical trials consecutively treated from 2011 to 2015 at the Drug Development Unit of the Royal Marsden Hospital. Cox regression analysis was performed to examine the relationship between overall survival (OS) and baseline characteristics, treating the occurrence of grade III/IV EAs as a time-varying covariate. Results: The most common emergent EAs (all grades) were as follows: hyponatraemia 62%, hypokalaemia 40%, hypophosphataemia 32%, hypomagnesaemia 17% and hypocalcaemia 12%. Grade III/IV EAs occurred in 19% of cases. Grade III/IV EAs occurred during the dose-limiting toxicity window in 8.46% of cases. Diarrhoea was associated with hypomagnesaemia at all grades (p < 0.001), hyponatraemia at all grades (p = 0.006) and with G3/G4 hypokalaemia (p = 0.02). Baseline hypoalbuminaemia and hyponatraemia were associated with a higher risk of developing other EAs during the trial in the univariate analysis. Patients who developed grade III/IV EAs during follow-up had an inferior median OS (26 weeks vs 37 weeks, hazard ratio = 1.61; p < 0.001). Conclusion: This is the first study to demonstrate the clinical significance of baseline hypoalbuminaemia and hyponatraemia, which are predictors of development of other EAs in phase I patients. Grade III/IV EAs are adverse prognostic factors of OS independent of serum albumin levels. Highlights: Patients who develop grade III/IV electrolyte abnormalities have poorer overall survival. Hyponatraemia is linked to higher risk of developing other electrolyte abnormalities. Hypoalbuminaemia is linked to higher risk of developing electrolyte abnormalities.